Еволюція розвитку та сучасні тренди в управлінні проектами - Краснокутська, Наталія Станіславівна; Осетрова, Тетяна Олександрівна (Тернопільський національний економічний університет, 2018)
Вступ. Розуміння історичних етапів формування методів управління проектами необхідно для визначення його ключових характеристик і особливостей. Такий підхід дає можливість виявити закономірності розвитку суспільства у зв'язку із поширенням принципів управління проектами, виокремити області, які не були розглянуті в наукових роботах у достатньому обсязі, а також визначити основні тенденції розвитку методології управління проектами. Мета. Метою статті є дослідження розвитку методології управління проектами, здійснення його періодизації із визначенням основних подій, що вплинули на управлінські практики, а також формування власного погляду на сучасні тенденції проектного управління. Метод (методологія). Для досягнення поставленої мети були використані загальнонаукові методи, зокрема методи аналізу та синтезу, системного підходу, графічний метод. Результати. Обґрунтовано періодизацію підходів і методів управління проектами, систематизовано його основні концепції, розроблені у наукових працях протягом 1960-2000-х років, проаналізовано результати успішності проектів за останні 20 років та обґрунтовано основні тенденції розвитку проектного менеджменту.

Introduction. Understanding of the historical stages of the formation of project management methods is necessary to determine its key characteristics and peculiarities. This approach makes it possible to identify the laws of development of society in connection with the distribution of the principles of project management, to identify areas that are not considered in scientific works in sufficient quantities, as well as to identify the main trends in the development of project management methodology. Purpose. The article aims to study the development of the methodology of project management, to implement its periodization with the identification of major events that have influenced management practices, as well as the formation of the own view as for the current trends in project management. Method (methodology). In order to achieve the goal, such common scientific methods as method of analysis and synthesis, method of system approach, graphical method have been used in the research. Results. The periodization of approaches and methods of project management have been substantiated. Its main concepts have been systematized. These concepts have been developed in scientific works during the 1960-2000s. The results of successful projects over the last 20 years have been analysed. The main tendencies of project management development have been grounded.
Evolution of development and current trends in project management
Keywords: управління проектами; еволюція проектного менеджменту; адаптація; тренди; project management trends; project management; evolution of project management; adaptation; trends